301 Natural History and Treatments of The Pediatrics' Deep-Seated Brain Arteriovenous Malformations. (April 2023) - Sattari, Shahab Aldin; Yang, Wuyang; Feghali, James; Xu, Risheng; Huang, Judy
Abstract : INTRODUCTION: Literature is sparse about the hemorrhage risk associated with the pediatrics' deep-seated brain AVMs (bAVMs) during the natural history and after treatment. METHODS: We retrospectively reviewed our institutional bAVM database from 1990 to 2019 and included pediatrics who had deep-seated bAVMs. We presented the annual hemorrhage risk; during the natural history and after treatments, and functional outcomes. RESULTS: After the screening of 914 patients, 31 pediatric cases; including 13 males and 18 females, with the mean (SD) age of 11.8 (4.4) were included. The most frequent presenting symptoms were headache (54.83%), weakness (38.7%), and seizure (22.5%). The mean (SD) of followed-up duration was 13.14 (12.5) years, during which 7(22.5%) AVMs were found obliterated, 10 (32.2%) individuals sustained hemorrhage, and the modified Rankin Score (mRS) worsened in 8 (25.8%) patients. The annual hemorrhage risk of natural history was 3.26% per patient, and the overall annual hemorrhage risk after treatment was 1.97% per patient. The annual hemorrhage risk in each treatment group was 0.64% per patient in radiosurgery, 6.3% per patient in surgery, and 6.29% per patient in embolization. Those with non-white race showed a trend of higher ruptured presentation (OR = 5 [0.84-41.68], p = 0.09). Female sex was associated with higher (OR = 13.076 [1.424-333.591], p = 0.048) and treatment radiosurgery was associated with lower (OR = 0.21 [0.03-1.02], p = 0.06) odds of follow-up hemorrhage. Headache presentation was associated with the lower odds of poor functional outcome (OR = 0.102 [0.011-0.670], p = 0.024). CONCLUSIONS: Given the substantial cumulative risk of lifelong hemorrhagic stroke in pediatric patients, timely definitive treatment is warranted. Radiosurgery treatment is beneficial when the risk-benefit profile is deemed favorable.